Autophagy mediates temporary reprogramming and dedifferentiation in plant somatic cells. (13th January 2020) - Rodriguez, Eleazar; Chevalier, Jonathan; Olsen, Jakob; Ansbøl, Jeppe; Kapousidou, Vaitsa; Zuo, Zhangli; Svenning, Steingrim; Loefke, Christian; Koemeda, Stefanie; Drozdowskyj, Pedro Serrano; Jez, Jakub; Durnberger, Gerhard; et al.
Abstract: Somatic cells acclimate to changes in the environment by temporary reprogramming. Much has been learned about transcription factors that induce these cell‐state switches in both plants and animals, but how cells rapidly modulate their proteome remains elusive. Here, we show rapid induction of autophagy during temporary reprogramming in plants triggered by phytohormones, immune, and danger signals. Quantitative proteomics following sequential reprogramming revealed that autophagy is required for timely decay of previous cellular states and for tweaking the proteome to acclimate to the new conditions. Signatures of previous cellular programs thus persist in autophagy‐deficient cells, affecting cellular decision‐making. Concordantly, autophagy‐deficient cells fail to acclimatize to dynamic climate changes. Similarly, they have defects in dedifferentiating into pluripotent stem cells, and redifferentiation during organogenesis. These observations indicate that autophagy mediates cell‐state switches that underlie somatic cell reprogramming in plants and possibly other organisms, and thereby promotes phenotypic plasticity. Synopsis: Adjustment to new environmental signals requires temporary and rapid modulation of the cellular proteome. Proteome adjustments are found to require autophagy, which erases previous cellular states in plant somatic cells to allow new programs to unfold. Multiple external stimuli rapidly activate autophagy in plant cells. Proteome adjustments during cell‐state switching are disrupted in autophagy mutants. Autophagy‐deficient plants exhibit decreased phenotypic plasticity. Autophagy‐deficient somatic cells cannot de‐differentiate efficiently into pluripotent stem cells. Exit from pluripotency and organ formation are dysregulated in autophagy‐deficient cells. Abstract : Autophagy facilitates cellular proteome adjustment to new stimuli and allows coordinated transition to a new cell state by erasing previous cellular programs.